Perspectives on gender, migration and transnational work: joint work of social reproduction and care in Southern Europe - Barañano Cid, Margarita; Marchetti, Sabrina (Investigaciones Feministas (Feminist Research), 2016)
This paper presents the "state of the art" and some of the main issues discussed in relation to the topic of transnational migration and reproductive work in southern Europe. We start doing a genealogy of the complex theoretical development leading to the consolidation of the research program, linking consideration of gender with transnational migration and transformation of work and ways of survival, thus making the production aspects as reproductive, in a context of globalization. The analysis of the process of multiscale reconfiguration of social reproduction and care, with particular attention to its present global dimension is presented, pointing to the turning point of this line of research that would have taken place with the beginning of this century, with the rise notions such as "global care chains" (Hochschild, 2001), or "care drain" (Ehrenreich and Hochschild, 2013). Also, the role of this new agency, now composed in many cases women who migrate to other countries or continents, precisely to address these reproductive activities, is recognized. Finally, reference is made to some of the new conceptual and theoretical developments in this area.